2012
DOI: 10.1016/j.ajpath.2011.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Aquaporin-4 Augments Cytotoxic Brain Edema after Traumatic Brain Injury during Acute Ethanol Exposure

Abstract: We previously reported that ethanol consumption affects morbidity and mortality after traumatic brain injury (TBI) by accelerating brain edema via oxidative stress after TBI. Aquaporin-4 (AQP4), a water channel, is involved in brain edema formation. In this study, we found that acute ethanol administration increased AQP4 expression after TBI, leading to severe brain edema in rats. Rats were pretreated with ethanol (3 g/kg) or dl-buthionine-(S,R)-sulfoximine (BSO; 100 mg/kg), an oxidative stressor, before TBI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Astroglial cells in culture swell due to ethanol exposure and withdrawal, but previous evidence of blockade by diuretics has been conflicting [59], [60]. However, acceleration of trauma-related cerebral edema by ethanol has been linked to increased AQP4 upregulation and activity, with acetazolamide, presumably through inhibition of AQP4, exerting protection [61]. Herein, binge ethanol-induced AQP4 elevations in brain regions that sustain neurodegeneration, but not in regions known to lack neurodamage, indicate that the water channel could be an important factor in the regioselective neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Astroglial cells in culture swell due to ethanol exposure and withdrawal, but previous evidence of blockade by diuretics has been conflicting [59], [60]. However, acceleration of trauma-related cerebral edema by ethanol has been linked to increased AQP4 upregulation and activity, with acetazolamide, presumably through inhibition of AQP4, exerting protection [61]. Herein, binge ethanol-induced AQP4 elevations in brain regions that sustain neurodegeneration, but not in regions known to lack neurodamage, indicate that the water channel could be an important factor in the regioselective neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ethanol has been shown to be associated with respiratory depression, apnoea and hypoxia [3][4][5], which may contribute to secondary insults following TBI. Raised intracranial pressures and acidaemia have also been reported as potential adverse effects of ethanol exposure [6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…Known connections between increased AQP4 and cytotoxic (cellular) edema [13] led to our considering that alcohol binges were precipitating cerebral edema via potentiation of the water channel, and indeed, initial immunoblots indicated higher AQP4 levels in alcohol-treated brain slices in culture [10]. Other reports have shown that increased AQP4 is important in alcohol’s augmentation of traumatic brain injury and edema [14] and in pro-inflammatory cytokine elevations in lipopolysaccharide-induced neuroinflammation [15]. Thus AQP4, like PLA2 below, can function as a potential neuroinflammatory stimulus.…”
mentioning
confidence: 99%